HISTOPATHOLOGY IN THE GUT OF SILKWORM, Bombyx mori Linn. INFECTED WITH MICROSPORIDIA (Applied Biological Research, 2023)
A number of microsporidia have been reported as infecting the gut of silkworm and then passing to  the other organs via gut wall (Kawarabatta, 2003; Bhat, 2006). However, in most cases such reports  have been dealt more with the development of microsporidians with little emphasis on host parasite  interaction. Microsporidia (Msp) isolated from economically important insect silkworm, Bombyx  mori infects the cytoplasmic cells of gut causing histopathological alterations (Kamili et al., 2009,  2010). This paper describes the ultrastructural histopathological changes observed in microspordian  infected tissues of the silkworm.
Keywords: HISTOPATHOLOGY; SILKWORM; INFECTED; MICROSPORIDIA